Research Progress on the Stability of Coalbed Methane Wells: From Theoretical Models to Numerical Simulation - Li, Mengna (Scientific Journal of Technology, 2026)
As coalbed methane exploration and development advance into deeper and more geologically complex areas, borehole stability has become one of the core technical bottlenecks restricting the safe and efficient development of coalbed methane. This paper systematically reviews recent research progress in the field of coalbed methane wellbore stability, with a focus on two main directions: mechanical analysis models and numerical simulation methods. First, it elaborates in detail on five types of mechanical models based on approximate strength theory, fracture damage mechanics, weak plane structures, discontinuous media, and fracture mechanics, analyzing the theoretical foundations, applicable conditions, and their applications and limitations in evaluating coal seam wellbore stability. Second, it provides an overview of early international numerical simulation studies represented by software such as FLAC and STAB-ViewTM, and then comprehensively summarizes the latest applications of multi-physics field numerical simulation techniques—including discrete element method, finite element method, RFPA, and COMSOL—in research on coalbed methane wellbore stability, revealing the influence mechanisms of factors such as in-situ stress, joint systems, drilling fluid parameters, and multi-field coupling effects on borehole stability. Finally, in light of the current engineering requirements for deep coalbed methane horizontal well development, it points out deficiencies in existing research regarding the adaptability of theoretical models, multi-field coupling mechanisms, and intelligent prediction methods, and provides an outlook on future research directions, aiming to offer theoretical support and methodological reference for the optimized design and risk control of coalbed methane drilling engineering.